Consumer behavior research on traditional foods in Africa: A scoping review - Arnold Moyo; Felix Amoah; Marlé van Eyk (Cogent Business & Management, 2023)
The aim of this scoping review was to identify and consolidate existing empirical evidence on consumer behavior research regarding traditional foods in Africa, with a view to contributing to the advancement of further research in the area. More specifically, the study sought to map the extent of available evidence, establish the nature of research topics and identify theories and models upon which identified studies were based. While results showed a general scarcity of empirical studies on consumer behavior towards traditional foods in Africa, the last five years have recorded a sustained increase in research. Nigeria, South Africa and Kenya are the main contributors to this research. Most of the research focused on sensory attributes of traditional foods and how they were perceived, evaluated and liked/disliked by consumers. There was also significant research exploring cognitive aspects underlying consumer behavior. However, the use of established theory or models in framing existing research was minimal.
Keywords: 650; Africa; consumer behavior; scoping review; Traditional food